Digital technologies for the assessment of cognition: A clinical review - Chinner, A; Blane, J; Lancaster, C; Hinds, C; Koychev, I (BMJ Publishing Group, 2018)
Dementia is the most widespread neurodegenerative disorder globally, and is associated with an immense societal and personal cost. With dementia prevalence projected to triple worldwide by 2050, there is an urgent need to increase the efficacy of dementia prevention, treatment and care. Rapid advancements in digital technology is starting to provide new opportunities to alleviate some of the challenges faced by dementia clinicians and researchers. This clinical review aims to summarise the current evidence for the use of pervasive digital technologies to monitor and support cognition in pre-clinical, prodromal and demented populations. Generally, the digital technologies provided valid measures of users’ cognitive function. However, most of the systems are still in the initial development stages, with limited data on acceptability in patients. Although the use of digital technology to monitor and support cognitive domains affected by dementia is a promising area of development, additional research validating the efficacy, utility and cost-effectiveness of these systems in patient populations is needed.